Performance of Earthworm (Lumbricus rubellus) During Different Transportation Durations - W. Marnelis; R. Afnan; V. A. Mendrofa (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
Earthworms (Lumbricus rubellus) are one of the soil organisms with a protein content of approximately 76%, providing significant benefits to human life. It is necessary to transport livestock/animals from their place of origin to the destination for processing or further cultivation in order to maximize the utilize of earthworms. During transportation, various challenges are encountered, leading to a decline in the performance of earthworms. The aimed of this research was to study the influence of different transportation durations on the performance of earthworms. A Completely Randomized Design (CRD) was employed with three different transportation duration treatments and three replications. Further analysis would be conducted using Duncan’s multiple-range test if the results differred significantly. Variables observed in this study included the conditions of the media pH, media temperature and humidity, environmental temperature, and humidity, weight loss and earthworm mortality. The results indicated that transportation duration significantly differs (P<0.05) in affecteding the weight loss and mortality earthworms. The 3-hour transportation treatment resulted in the highest weight loss (82.33 g, equivalent to 55.63%) and mortality (411.87 g, equivalent to 91.07%).